Analysis of Moment of Truth in Culinary Tourism Destination: A Case of Haitang Bay Houhai Fishing Village Hainan, China - Benediktus Adhityawarman; Yustisia Pasfatima Mbulu; Andaru Puan Bhanuwati; Nasywa Arafvianti; Rifa Tiara Zahra (Research and Community Service Center, Politeknik Pariwisata NHI Bandung, 2025)
Moment of Truth is one way to market a tourist destination. The purpose of this research is to analyse the stages of Zero Moment of Truth, First Moment of Truth, Second Moment of Truth, and Ultimate Moment of Truth that tourists go through when deciding to visit Haitang Bay Houhai Fishing Village Hainan, China, for a culinary tour. This research uses a qualitative method, and the research data is obtained from interviews with tourists who come and direct observation to Haitang Bay Houhai Fishing Village Hainan, China, and the website. Based on the results of the study, it can be concluded that the series of Moment of Truth felt by tourists towards culinary tourism in Haitang Bay Houhai Fishing Village Hainan, China, has been passed and felt by tourists who visit there. The series of Moment of Truth that occurs is starting from the Zero Moment of Truth, First Moment of Truth, Second Moment of Truth, and Ultimate Moment of Truth stages, where tourists start looking for information related to the culinary available at Haitang Bay Houhai Fishing Village Hainan, China via mobile phones, then after seeing the available culinary tourism information, tourists decide to visit Haitang Bay Houhai Fishing Village based on the culinary information there that has been searched. Tourists directly taste and enjoy the culinary specialties at Haitang Bay Houhai Fishing Village. Finally, tourists give their reviews based on their experiences and the typical culinary they enjoy at Haitang Bay Houhai Fishing Village in Hainan, China, as well as recommending it to friends/family on social media. Based on the interview results, many tourists gave positive reviews and recommended to others about the culinary delights available. However, some tourists gave negative reviews and did not recommend Haitang Bay Houhai Fishing Village to come on a culinary tour there.